Identification of subtypes for the behavioral variant of frontotemporal dementia based on the assessment of disinhibition and compulsion: Neuropsychiatry and behavioral neurology: DLB and FTD ‒ clinical manifestations. (7th December 2020) - Godefroy, Valérie; Tanguy, Delphine; Sezer, Idil; Ber, Isabelle Le; Bouzigues, Arabella; Rametti‐Lacroux, Armelle; Carle, Guilhem; Azuar, Carole; Bendetowicz, David; Levy, Richard; Batrancourt, Bénédicte; Migliaccio, Raffaella
Abstract: Background: The behavioral variant of frontotemporal dementia (bvFTD) is characterized by cognitive and behavioral decline due to the progressive brain damage of frontal and temporal regions. We aimed to: 1. identify bvFTD subtypes through the behavioral assessment of social disinhibition and perseveration/compulsion; 2. disentangle the underlying functional and anatomical correlates. Method: We assessed occurrences of 19 behaviors (derived from current clinical criteria of bvFTD) linked to disinhibition and perseveration/compulsion in a quasi‐ecological setting in 17 bvFTD patients and 16 healthy controls (HC). Subjects also underwent neurocognitive tests and a structural MRI examination. Dimensions extracted through Principal Component Analysis from the behavior variables were compared between patients and HC. A clustering approach applied to behavioral scores allowed to isolate subgroups within the patients. Voxel based morphometry (VBM) was performed to identify specific grey matter atrophy patterns in each subgroup. Result: We identified two principal behavioral dimensions significantly different between bvFTD and HC. Using scores on these two components (labelled as Compulsion and Disinhibition), we identified two different subgroups of bvFTD patients (bvFTD‐G1 and bvFTD‐G2). BvFTD‐G1, characterized by high Disinhibition, had a small pattern of atrophy, centered on left medial anterior and posterior temporal cortices. BvFTD‐G2, characterized by high Compulsion and cognitive impulsivity, presented a more diffuse and bilateral atrophy pattern largely involving frontotemporal and subcortical regions. Conclusion: The behavioral assessment of disinhibition and compulsion symptoms allowed the clinical stratification of bvFTD patients into more or less severe stages or forms, and the identification of specific brain circuits associated with disinhibition and compulsion.